Case report: Development of anxiety symptoms after receiving the Pfizer-BioNTech (BNT162b2) COVID-19 vaccine: a case series - Taube, Maris; Lesiņa, Alise Alma (Frontiers in Psychiatry, 2025)
Severe acute respiratory sindrome - Coronavirus - 2 (SARS-CoV-2) (Coronavirus disease - 19 (COVID-19)) infection can result in long-term health consequences, such as long COVID. The clinical manifestations of long COVID include depression, anxiety, brain fog with cognitive dysfunction, memory issues, and fatigue. However, the links between vaccination and psychiatric disorders have been less studied. This article describes three patients who reported anxiety after receiving a complete course of the Pfizer-BioNTech BNT162b2 vaccine. It is important to explore the relationship between anxiety, other mental health disorders, and COVID-19 vaccination, as well as to investigate potential pathogenetic mechanisms.